(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Aim: This preliminary randomized, prospective, controlled trial aimed to compare the radiographic outcomes of three different disinfection protocols in the treatment of mature permanent teeth with necrotic pulps. Methodology: The trial has been reported according to the Preferred Reporting Items for Randomized Trials in Endodontics 2021 guidelines. The study protocol was registered at the clinical trial registry (ClinicalTrials.gov) with identifier number NCT05557994. Thirty-six patients with mature necrotic anterior teeth with large periapical lesions were randomly allocated into three groups (n = 12): group A, disinfected with triple antibiotic paste, group B, disinfected with activation of Xp-endo finisher, and group C, disinfected using diode laser. The follow-up was for 12 months. Peri-radicular healing was assessed using standardized radiographs taken at baseline, and at 6 and 12 months after treatment. Statistical analysis was conducted using the Kruskal-Wallis test followed by Dunn’s post hoc test with Bonferroni correction for intergroup comparisons and Freidman’s test followed by Nemenyi post hoc test for intragroup comparisons. The significance level was set at p ≤ .05 within all tests. Results: There was a significant increase in peri-radicular healing in all groups at 6 and 12 months, compared to that at baseline (p < .001). Conclusions: The findings of this preliminary trial indicate the potential for using single visit REPs using diode laser disinfection as a treatment option for mature teeth with necrotic pulps. A higher level of evidence obtained through adequately powered clinical trials and longer follow-up periods are required to conclusively validate the different outcomes of REPs.